RAPD Marker Assisted Study on Genetic Diversity of Indigenous Chilli (Capsicum sp.) Landraces of Nagaland, India - Orenthung, N.; Changkija, Sapu (International Journal of Bio-resource and Stress Management, 2023)
Random Amplified Polymorphic DNA (RAPD) analysis was carried out with sixteen promising chilli landraces comprising of three Capsicum chinense, five Capsicum frutescens and eight Capsicum annuum to study the inter and intra-specific genetic diversity. The RAPD analysis produced a total of 114 bands, out of which 109 bands were polymorphic indicating high level of polymorphism (95.6%). The average PIC value of the primers was 0.75 indicating that the markers were able to distinguish a high degree of variation. Jacquard’s similarity matrix constructed using Software NTSYS-pc, version 1.7. Rohlf (1992) showed a similarity coefficient ranging from 2.682-8.378, indicating high degree of variability among the chilli landraces evaluated. Dendrogram generated from Jaccard’s similarity coefficient matrix using UPGMA clustering method showed two major clusters. Cluster I include three Capsicum chinense and cluster II included both Capsicum annuum and Capsicum frutescens landraces. Cluster II was further sub-divided into two sub-clusters, Sub-cluster II A included five Capsicum frutescens landraces and sub-cluster II B included eight Capsicum annuum landraces. The grouping of the three species viz. Capsicum chinense, Capsicum frutescens and Capsicum annuum into three separate clusters at species level by the molecular analysis corresponds and support the morphology based grouping of the three chilli species by Smith and Heiser (1951). The RAPD marker system detected two unique bands detected by primer OPA-01 for chilli landrace NCL-05 (Capsicum frutescens) and Primer OPA-02 detected one band, unique to all chilli landraces belonging to Capsicum chinense.